ELECTION, MONEY POLITICSAND THE IMPLICATIONS FOR SUSTAINABILITY OF DEMOCRACY IN NIGERIA - Ayo Awopeju; Lawrence Olugbenga Martins (International Studies Journal)
Although money politics contributes significantly to democracy, it also has negative impact on sustaining democracy in developing democracies such as Nigeria and other African countries. Due to this, the study examines the antecedents of money politics with a view to establishing the reasons responsible for money politics, the strengths and shortcomings of money politics and the implications it has on sustaining democracy in Nigeria. Making use of secondary sources of data, the study found out that increase in population cum high value of money, increase in number of political parties, high intensity of electoral contests and desperation to control government by political class are the factors responsible for money bag politics. Despite the fact that money politics hasthe strengths, it has implications of encouraging looters, eroding competence of the candidate, weakening political participation and undermining democratic governance in Nigeria. The study concludes that unregulated money politics in elections by political parties and politicians has debilitating impact on sustaining democracy and that it is only the hostile stance of government that can completely root out the pervasive money bag politics in Nigeria. The study recommends that government should redesign the framework of money bag politics in order to ensure strict compliance by the political parties and other stakeholders in the conduct of election in Nigeria.